ON THE NATURE OF NON-RESPONDING IN DISCRIMINATION LEARNING WITH AND WITHOUT ERRORS - Terrace, H. S. (Journal of the experimental analysis of behavior, 1974)
In human subjects, discrimination learning with errors results in active responding incompatible with the reinforced response. The direction of such incompatible behavior is opposite to that of the reinforced response. Responding occurs only during the stimulus correlated with extinction. The frequency of active non-responding is maximal shortly after the start of discrimination training (the time at which the frequency of errors decreases most rapidly) and approaches zero as discrimination training continues. The magnitude of behavioral contrast is not related systematically to the number of errors. Instead it is related directly to the frequency of active non-responding. Active non-responding appears to be motivated by the aversiveness of self-produced frustration, in the sense that active non-responding allows the subject to avoid the aversiveness of non-reinforced responding.